The Computer Generation's Willingness to Pay for Originals when Pirates are Present – A CV study - Håkan J. Holm (Lund University, School of Economics and Management, Department of Economics, 2000)
A contingent valuation method is applied to study subjects' willingness to pay for originals when illegal copies are freely available. The subjects consisted of 234 Swedish undergraduate students from the "computer generation". Only 2% of the "normal" (and 0% of the "elite") students were willing to pay the retail price for the original. However, the majority was prepared to pay a non-negligible amount for the original. Demand curves and profit maximizing behaviors are analyzed. The price elasticity of piracy indicates that piracy is insensitive to price cuts. The results have implications for the calculation of damages of piracy.
Keywords: D40; K40; K42; L20; Z10; 330; Piracy; Contingent Valuation; Damages; Software